Theranostics Nuclear Medicine in Prostate Cancer - Helena Lima; Marina Etchebehere; Mateos Bogoni; Caroline Torricelli; Ellen Nogueira-Lima; Victor M. Deflon; Mariana Lima; Elba Etchebehere (MDPI AG, 2024)
Theranostic Nuclear Medicine is based on the idea of combining the same molecule (or drug) with different radioisotopes for both diagnosis and treatment, a concept that emerged in the early 1940s with the use of radioactive iodine for thyroid diseases. Theranostic Nuclear Medicine has since expanded to diseases of higher incidence, such as prostate cancer, with several imaging methods used to assess the extent of the disease and the corresponding radiopharmaceuticals used for treatment. For example, by detecting osteoblastic metastases by bone scintigraphy, corresponding radiopharmaceuticals with therapeutic properties can be administered to eliminate or reduce pain associated with metastases and/or determine overall survival gain. The purpose of this review is to discuss the role of Theranostic Nuclear Medicine in prostate cancer, addressing the main diagnostic imaging studies with their corresponding treatments in the Theranostic model.